2015
DOI: 10.1186/s12952-015-0023-y
|View full text |Cite
|
Sign up to set email alerts
|

No effects of a 12-week supervised exercise therapy program on gait in patients with mild to moderate osteoarthritis: a secondary analysis of a randomized trial

Abstract: BackgroundIt is unknown whether gait biomechanics in hip osteoarthritis patients with mild to moderate symptoms change following exercise therapy interventions. The aim of the present study was to compare stance phase gait characteristics in hip osteoarthritis patients with mild to moderate symptoms participating in a randomized trial with two different interventions; patient education only or patient education followed by a 12-week supervised exercise therapy program.ResultsThe study was conducted as a second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
7
1
Order By: Relevance
“…Group-based interventions may improve outcomes by increasing compliance compared to individual-based interventions [ 33 ]. Eitzen et al found no effect of a 12-week supervised education and exercise therapy program on gait in patients with osteoarthritis, but the exercise component was delivered individually and resulted in low compliance while the education component was group-based and showed 100% compliance [ 34 ]. Even over the course of a year, a community-based water exercise program achieved 70% compliance for the twice-a-week group sessions [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Group-based interventions may improve outcomes by increasing compliance compared to individual-based interventions [ 33 ]. Eitzen et al found no effect of a 12-week supervised education and exercise therapy program on gait in patients with osteoarthritis, but the exercise component was delivered individually and resulted in low compliance while the education component was group-based and showed 100% compliance [ 34 ]. Even over the course of a year, a community-based water exercise program achieved 70% compliance for the twice-a-week group sessions [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although numerous studies have shown that HOAP adopt characteristic compensation strategies, their relation to load alterations in the knee and hip joint have not been satisfactorily established. Clarification of the latter would seem beneficial, as physical exercise and gait retraining programs often fail . Because HOAP retain their pre‐operative gait patterns for several years after hip joint replacement, these patients may be disproportionally at higher risk for abnormal joint loading and thus for the development of OA in other joints of the lower extremities .…”
Section: Discussionmentioning
confidence: 99%
“…Conservative management of HOAP, like physical exercise programs and gait retraining, is complex . To do so, it is beneficial to gather detailed information about factors that impact asymmetrical knee and hip joint loading.…”
mentioning
confidence: 99%
“…The failure of the ACL‐SPORTS training program to restore symmetry in every knee gait biomechanical variable assessed following training, at only 7 months after primary ACLR, may be unremarkable in light of the findings from Kaur et al Other post‐operative rehabilitation interventions also have been unsuccessful at improving gait biomechanics in various populations. For example, Eitzen et al found a 12‐week supervised exercises therapy program did not change frontal or sagittal plane hip, knee, or ankle kinematics or kinetics in patients with hip osteoarthritis. Previous studies investigating strength and perturbation training on gait mechanics in ACL‐deficient participants have found a greater response in women compared to men, who walked with similar patterns before and after training .…”
Section: Discussionmentioning
confidence: 99%